Re-examining the youth program quality survey as a tool to assess quality within youth programming - Bean, Corliss; Forneris, Tanya (Université d'Ottawa | University of Ottawa, 2016)
The Youth Program Quality Survey is a 24-item measure of program quality designed to evaluate participant perceptions of experiences in short- and longterm youth programs. The Youth Program Quality Survey was developed based on the National Research Council and Institute of Medicine’s eight program setting features that can contribute to the positive development of youth. This measurement tool is quite new within the field and as such little research has been conducted to determine its validity and reliability. The current study is designed to examine three previously proposed factor structures with a sample of 391 youth between the ages of 10 and 18 who participated in 38 different youth programs (e.g. sport, leadership, in-school-mentoring). Confirmatory factor analysis results indicate model fit issues with all three proposed factor structures. Therefore, an exploratory factor analysis is performed to improve model fit, and a revised 4-factor 19-item model is proposed. An analysis of invariance by age shows that the measurement model did not vary between younger and older youth participants. Practical implications and areas of future research are offered.
Keywords: adolescence; exploratory factor analysis; program quality; evaluation